Reciprocity in dynamics of supramolecular biosystems for the clustering of ligands and receptors - Shikha Dhiman; Marle E. J. Vleugels; Richard A. J. Post; Martina Crippa; Annalisa Cardellini; Esmee de Korver; Lu Su; Anja R. A. Palmans; Giovanni M. Pavan; Remco W. van der Hofstad; Lorenzo Albertazzi; E. W. Meijer (Proceedings of the National Academy of Sciences, 2025)
Multivalent binding and the resulting dynamical clustering of receptors and ligands are known to be key features in biological interactions. For optimizing biomaterials capable of similar dynamical features, it is essential to understand the first step of these interactions, namely the multivalent molecular recognition between ligands and cell receptors. Here, we present the reciprocal cooperation between dynamic ligands in supramolecular polymers and dynamic receptors in model cell membranes, determining molecular recognition and multivalent binding via receptor clustering. The nonlinear dependences of the ligand concentration, receptors, and their binding affinity are observed experimentally by fluorescence and superresolution fluorescence microscopies, revealing a valency-dependent clustering mode of anchoring. The mechanism is supported by stochastic modeling demonstrating that such nonlinear dependence is unlikely in the absence of any dynamics and superselectivity. Using a coarse-grained molecular model, the subtle competition between local and global entropies that controls this anchoring mechanism explains the clustering. Further investigation using single particle tracking reveals the presence of two populations of bound and unbound receptors after the clustering process. The result of this study highlights the importance of reciprocity of dynamics in supramolecular polymer and lipid membrane for recruitment, multivalent binding, and clustering, all of which are crucial elements in the design of materials capable of actively interacting with biological targets.